Pengembangan Gerakan Madrasah Membaca (GMM) dengan Program Literasi Perpustakaan (PLP) - Ahwy Oktradiksa; Mujahidun Mujahidun (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The objectives of this service are 1) increasing knowledge and understanding of the madrasah reading movement based on library management, 2) increasing madrasa library management services, 3) increasing the ability of library management resources, 4) increasing madrasah services in implementing the madrasa reading movement. The method of implementing this trial uses a participation rular appraisal approach, which is a method of involving various elements that are considered to contribute in submitting ideas, ideas for the smooth running of a service program. The results of the service implementation consist of four solution programs that have been implemented, namely 1) problem mapping with the discovery of what potential can be realized together through a group discussion forum agenda, 2) assistance for reading/literacy movement programs for madrasas in collaboration with the University of Muhammadiyah Magelang (UNIMMA) library and Regional Library (Perpusda) Magelang Regency, 3) strengthening library resource services in collaboration with the University of Muhammadiyah Magelang library, 4) performance program follow-up plans, namely the madrasa reading movement which began with the madrasa library organizational structure, book donation movement by student guardians, committee management madrasas and PRM and PCM, improving library infrastructure (rooms, shelves, book layouts, and preparing library corners in the corner of the classroom), mosaic competitions, speed reading, coloring, story-telling, and assistance in making proposals for collaboration.